Templated Sub‐100‐nm‐Thick Double‐Gyroid Structure from Si‐Containing Block Copolymer Thin Films. Issue 20 (6th April 2017) - Aissou, Karim; Mumtaz, Muhammad; Portale, Giuseppe; Brochon, Cyril; Cloutet, Eric; Fleury, Guillaume; Hadziioannou, Georges
Abstract : The directed self‐assembly of diblock copolymer chains (poly(1, 1‐dimethyl silacyclobutane)‐ block ‐polystyrene, PDMSB‐ b ‐PS) into a thin film double gyroid structure is described. A decrease of the kinetics of a typical double‐wave pattern formation is reported within the 3D‐nanostructure when the film thickness on mesas is lower than the gyroid unit cell. However, optimization of the solvent‐vapor annealing process results in very large grains (over 10 µm²) with specific orientation (i.e., parallel to the air substrate) and direction (i.e., along the groove direction) of the characteristic (211) plane, demonstrated by templating sub‐100‐nm‐thick PDMSB‐ b ‐PS films. Abstract : The directed self‐assembly of diblock copolymer chains (poly(1, 1‐dimethyl silacyclobutane)‐ block ‐polystyrene, PDMSB‐ b ‐PS) into a thin‐film double‐gyroid structure is described. Optimization of the solvent‐vapor annealing process demonstrates very large grains (over 10 µm²) with specific orientation and direction of the characteristic (211) plane, by templating sub‐100‐nm‐thick PDMSB‐ b ‐PS films.